New Perspectives in Technology Transfer Theories, Concepts, and Practices in an Age of Complexity - Mietzner, Dana; Schultz, Christian (FGF Studies in Small Business and Entrepreneurship, 2021)
XII, 281 p. 37 illus., 18 illus. in color.